Modulação genética do bcl11a no perfil inflamatório, hemolítico, estresse oxidativo e nos níveis de hemoglobina fetal em pacientes com anemia falciforme - Machado, Rosângela Pinheiro Gonçalves (2015)
8 ABSTRACT Sickle cell disease (SCD) is an autosomal hereditary hemoglobinopathies caused by a point mutation in the beta globin gene generates an abnormal hemoglobin called hemoglobin S (Hb S) in homozygous. The disease is characterized by presenting a variability of symptoms, which is due to m ultiple factors, including fetal hemoglobin (HbF), the haplotypes of the beta globin gene and polymorphisms BCL11A gene, among others. The assessment of genetic modulators in AF has been developed in order to improve the understanding of its pathophysiolog y and direct therapeutic approach aiming his individualization. The research set out to determine the genetic modulation of polymorphisms BCL11A gene (rs4671393, rs7557939 and rs1186868) on the inflammatory profile, hemolytic, oxidative stress and the conc entrations of HbF, Hb in patients with AF, in steady state. The study was cross and analytical type with 42 adult patients receiving outpatient treatment at the University Hospital Walter Cantídio (HUWC), with molecular diagnostics and haplotypes of the be ta globin gene S previously realized. The patients were taking hydroxyurea (HU), on average 20 mg / kg body weight. Biological samples of peripheral blood were obtained for performing laboratory tests: The dosages of IL - 6 pro - inflammatory cytokine, IL - 17, TNF - alpha and IL - 10 and anti - inflammatory TGF - beta by ELISA; reticulocyte counts by the manual method, dosage methemoglobin (MetHb) and lactate dehydrogenase (LDH) by spectrophotometry; nitrite (NOx), malondialdehyde (MDA) serum, erythrocyte antioxidant en zymes catalase (CAT) and glutathione peroxidase (GPx) for kits and spectrophotometry. Genetic polymorphisms of BCL11A gene regions, rs4671393, rs7557939 and rs1186868 were determined by Real Time PCR. Dosages of HbF, and HbS were performed by HPLC (High Pe rformance Liquid Chromatography). The data age, sex and clinical events were obtained from medical records. All statistical analysis was performed using the free software R, in version 3.1.2. To analyze the frequency of sex and genotype by region and assoc iations between the type of haplotype and clinical events with the regions of BCL11A, they used the chi - square test and Fisher's exact. Held the ANOVA parametric test (obtained under distributional assumptions), and the non - parametric Kruskal - Wallis to ana lyze the association of genotypes BCL11A gene with age, the levels of Hb, HbF, inflammatory profile, hemolytic and oxidative stress. It was considered significant at the 5% level. Most patients (57.14%) were female. The age of the included patients was 18 - 65 years, mean and median value of 35.1 and 33 years respectively. Only rs7557939 of BCL11A, genotype A / G was the most prevalent and the prevalence of genotype A / G was higher in women, while in men the highest prevalence was genotype A / A. However, rs 1186868 of BCL11A, the majority (56.52%) of women had the C / T genotype and half the men showed the T / T genotype. No BCL11A region of the gene showed a significant association with haplotype S beta - globin gene Regarding gene BCL11A modução the levels of HbF, and HbS, it was found that there was a significant rs1186868 results in the mutant genotype T / T, showed higher levels o Hb and lower levels of HbF. In rs7557939 there was a significant decrease in HbF in the mutant allele A / A, however, there was no relationship with the HbS. There was no association between SNPs in the three regions studied, with the average number / median of inflammatory modulators, hemolysis markers of oxidative stress and clinical events at the level of 5% .The findings reinf orce the hypothesis of genetic modução of BCL11A gene polymorphisms in relation to levels of HbF, where the wild allele, rs7557939 and rs1186868 in the regions had a protective character in prognosis decorência of referral increased levels of HbF in patien ts with AF study.